2014
DOI: 10.1111/iwj.12289
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a large cohort of patients with diabetes having at‐risk feet and outcomes in patients with foot ulceration referred to a tertiary care diabetes unit

Abstract: To identify in a large population cohort the clinical and biochemical characteristics of patients with diabetes at risk of foot ulceration and outcomes in those with foot ulcers. All patients with diabetes attending Baqai Institute of Diabetology and Endocrinology from January 2004 to April 2012 included in the study. Clinical, biochemical and socio-demographic data were collected and patients were categorised into those at no risk of ulceration, at risk of ulceration and those with foot ulcer, according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…Aziz et al reported an amputation rate of 28% in Singapore in their prospective study on 100 patients with diabetic foot infections treated at the National University Hospital of Singapore in 2011 . Riaz et al reported an amputation rate of 11% in Pakistan . Nather et al reported a 27·2% major amputation rate, and Zubair et al reported an overall amputation rate of 28·4% in a North Indian tertiary care hospital .…”
Section: Discussionmentioning
confidence: 99%
“…Aziz et al reported an amputation rate of 28% in Singapore in their prospective study on 100 patients with diabetic foot infections treated at the National University Hospital of Singapore in 2011 . Riaz et al reported an amputation rate of 11% in Pakistan . Nather et al reported a 27·2% major amputation rate, and Zubair et al reported an overall amputation rate of 28·4% in a North Indian tertiary care hospital .…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of anemia in people with type 2 diabetes was observed 63% in Sharif A et al study and in people with DFU it is 59.04% in Wright JA et al study, while 89.6% anemic people with DFU underwent amputations in Costa RH et al study 8,11,12. Limited studies have been done to observe the association of anaemia with DFU 13. To the best of our knowledge, none of the studies from Pakistan reported it.…”
Section: Introductionmentioning
confidence: 92%
“…There are several scores to determine the severity of the diabetic ulcers [19][20] . The most used and accepted globally are those of Wagner and PEDIS, which, together with the classification of the University of Texas, try to encompass all the main aspects involved in the foot injury of a diabetic patient, such as the presence of ulcers, ischemia, and infection [20][21][22] . In the present study, no patient was classified as Wagner's grade 5 and PEDIS grade I.…”
Section: Resultsmentioning
confidence: 99%